Seabird attacks contribute to calf mortality in a whale population - Piotto, María (2024)
Reports of seabirds attacking marine mammals have become frequent in the 2000s. Southern right whales Eubalaena australis off Península Valdés (PV), Argentina, have suffered the effects of micropredation by kelp gulls Larus dominicanus since at least the 1970s. During 2003-2013, this population experienced 9 yr of unprecedented high calf mortality. Using a 25 yr dataset (1995-2019) of focal follows of gull-whale interactions, we studied long-term changes in gull attack intensity (attacks h-1) and frequency, and explored whether they influenced calf mortality. We also asked whether calf mortality was affected by prey density at maternal feeding grounds during gestation. Applying Bayesian models, we found that the intensity and frequency of attacks increased significantly from 1995 to the 2000s, and that in 2004-2019, calves received 2.85 times as many attacks as did mothers. Moreover, attacks significantly contributed to increase the probability of calves dying, such that a year with average overall harassment had 2.26 times the mortality of a hypothetical year with no attacks. In years of high intensity and frequency of attacks, many older calves died near the end of the season, probably reflecting the cumulative effect of gull harassment on calf health. However, calf mortality was not affected by prey density, and extremely high mortality was not related to extremely high frequency or intensity of attacks, indicating that deaths are also influenced by other unidentified factors. These findings imply that chronic micropredation contributed to the unprecedented high calf mortality observed in PV and that other marine mammal populations experiencing seabird attacks could be threatened.